PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA PERUSAHAAN DENGAN KEPEMILIKAN ASING SEBAGAI VARIABEL MODERASI - Zakarias, Kelvin Lovender; Bimo, Irenius Dwinanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to analyze the effect of sustainability reports on the performance companies with foreign ownership as a moderating variable. This study uses companies listed on the Indonesia Stock Exchange in 2017-2019. Sampling in this study using purposive sampling method. The sample used is 31 companies that meet the criteria. Hypothesis testing in this study uses panel data regression analysis (balanced panel) which is processed in the statistics and data program, namely Stata 17. The results of panel data analysis explain that the sustainability report has a positive effect on company performance. In addition, this study also finds that foreign ownership doesn’t moderate sustainability reports on company performance